New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants - Amini, Sudabe; Nozari, Jamasb; Mandelshtam, Michail Yu.; Knížek, Miloš; Etemad, Vahid; Faccoli, Massimo (Zootaxa, 2017)
Bark and ambrosia beetles from the subfamily Scolytinae are among the most important pests in forests of Northern Iran. During investigations conducted in 2013–2016 in different parts of northern forests, the species Crypturgus cribrellus Reitter, Liparthrum bartschti Mühl, Scolytus varshalovitchi Michalski, Scolytus sulcifrons Rey, Scolytus triarmatus (Eggers) and Trypophloeus granulatus (Ratzeburg) were recorded for the first time in Iran; Trypophloeus and Liparthrum were new genera for Iran. As new host plants we found Zelkova sp. for Scolytus varshalovitchi, Michalski, Populus sp. for Liparthrum bartschti, Mühl, Alnus sp. and Pterocarya fraxinifolia for Taphrorychus lenkoranus Reitter, Pterocarya fraxinifolia for Ernoporicus caucasicus (Lindemann), Carpinus sp. for Pteleobius vittatus (Fabricius), Parrotia persica for Scolytus intricatus (Ratzeburg), Alnus sp. and Pterocarya fraxinifolia for Hypothenemus eruditus (Westwood).